2018
DOI: 10.1007/s00405-018-5020-6
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of skull vibration-induced nystagmus in normal subjects

Abstract: Healthy subjects do not generally develop to NR upon vibratory stimulation and only 20% of the subjects studied here developed any kind of NR, this being a slow and inconsistent response of low frequency. The establishment of normal values contributes to improve the orientation in clinical practice in the pathological population and this opens possibilities for tackling more reliable studies in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
3
16
0
2
Order By: Relevance
“…3 Typically, if the two labyrinths are intact, the neural response generated by the stimulus is the same in both ears and no nystagmus appears. 4 If the neural response from each labyrinth is asymmetrical (e.g., unilateral vestibular hypofunction) during stimulation, horizontal nystagmus in which the fast phase beats in the direction of the healthy ear may be observed. 4,5 The SVINT is performed in a vision denied condition, and the patient's eye movements are recorded for approximately 10 seconds with no stimulation to establish a baseline.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Typically, if the two labyrinths are intact, the neural response generated by the stimulus is the same in both ears and no nystagmus appears. 4 If the neural response from each labyrinth is asymmetrical (e.g., unilateral vestibular hypofunction) during stimulation, horizontal nystagmus in which the fast phase beats in the direction of the healthy ear may be observed. 4,5 The SVINT is performed in a vision denied condition, and the patient's eye movements are recorded for approximately 10 seconds with no stimulation to establish a baseline.…”
mentioning
confidence: 99%
“…4 If the neural response from each labyrinth is asymmetrical (e.g., unilateral vestibular hypofunction) during stimulation, horizontal nystagmus in which the fast phase beats in the direction of the healthy ear may be observed. 4,5 The SVINT is performed in a vision denied condition, and the patient's eye movements are recorded for approximately 10 seconds with no stimulation to establish a baseline. Following the baseline recording, vibration is applied to the mastoid for at least 10 seconds.…”
mentioning
confidence: 99%
“…Skull vibration stimulates both the otolith and canal structures, and instantaneously triggers nystagmus by inducing or augmenting a preexistent vestibular asymmetry. 79 Vibration-induced nystagmus may be observed in up to 20% of healthy controls, 80 and may be useful for screening children with hearing loss for vestibular asymmetry when combined with other tests of vestibular function. 81 …”
Section: Triggered Nystagmusmentioning
confidence: 99%
“…Moreover, Batuecas-Caletrío et al described a close relationship between the SVIN-SPV at 100 Hz and the difference of VHIT gains between the two ears [ 53 ]. Zamora et al described the parameters of SVINT in normal subjects and proposed a discriminant SVIN-SPV value of 2.2°/s [ 54 ].…”
Section: From 2011 Until Nowmentioning
confidence: 99%
“… Topographic stimulation: International consensus relies on the mastoids position [ 6 , 45 ], with some interest in the vertex position (mainly French and German teams). Frequency consensus: 100 Hz widely used (majority of publications [ 3 , 4 , 7 , 10 , 16 , 24 , 25 , 30 , 31 , 34 , 40 , 45 , 46 , 47 , 49 , 52 , 54 , 56 ]). The systematic study of frequency optimization, analyzing SVIN SPV in response to 10 Hz up to 800 Hz, performed by Dumas et al with the Mini-shaker device of B&K has confirmed this optimal frequency empirically accepted by many other authors [ 1 , 6 ] ( Figure 2 ) Inner ear structure contribution to the constitution of the nystagmus (SVIN): the SCC and particularly the horizontal SCC is the predominant structure affected by the 100 Hz vibration.…”
Section: Summary Of the Agreement And International Consensusmentioning
confidence: 99%